Q. 11 `5.0( 2 Votes )

Find , when

𝒳 = a (cos θ + θ sin θ ), 𝒴 = a (sin θ - θ cos θ)

Answer :

Theorem: y and x are given in a different variable that is θ . We can find by finding and and then dividing them to get the required thing.


=


= a(cosθ - (-θ sinθ + cosθ )) {by using product rule, while differentiating θcosθ }


= a(θsinθ ) ………..(1)



= a(-sinθ +θ cosθ +sinθ ) {by using product rule, while differentiating θcosθ }


= a× θcosθ ……….(2)


Dividing (1) and (2), we get


=


= tanθ ANS


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses